2008
DOI: 10.1038/ki.2008.303
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr inhibits cytokinesis in human proximal tubule cells

Abstract: HIV associated nephropathy (HIVAN) afflicts an estimated 1–3 million people worldwide and is a major cause of morbidity and mortality. Murine transgenic models have demonstrated that expression of HIV-1 genes in kidney cells results in characteristic HIVAN pathology: collapsing FSGS and microcystic tubular disease. While we have gained significant understanding of the podocyte disease, less is known about the tubular epithelial responses to infection. HIV-1 vpr plays an important role in the FSGS of HIVAN part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…Previous work using pseudotyped lentiviral particles expressing single---gene constructs, pHR---Vpr, pHR---Tat, or pHR---Vif, confirm that the G2 arrest phenotype is Vpr---specific in RTEC model systems [60]. …”
Section: Mechanisms Of Vpr-induced G 2 Arrest In the Kidneymentioning
confidence: 70%
See 3 more Smart Citations
“…Previous work using pseudotyped lentiviral particles expressing single---gene constructs, pHR---Vpr, pHR---Tat, or pHR---Vif, confirm that the G2 arrest phenotype is Vpr---specific in RTEC model systems [60]. …”
Section: Mechanisms Of Vpr-induced G 2 Arrest In the Kidneymentioning
confidence: 70%
“…Vpr---mediated arrest in the G2 phase of the cell cycle is well established in both immortalized and primary renal tubule epithelial cells [60,138,139]. Previous work using pseudotyped lentiviral particles expressing single---gene constructs, pHR---Vpr, pHR---Tat, or pHR---Vif, confirm that the G2 arrest phenotype is Vpr---specific in RTEC model systems [60].…”
Section: Mechanisms Of Vpr-induced G 2 Arrest In the Kidneymentioning
confidence: 85%
See 2 more Smart Citations
“…Its expression in tubular epithelial cells is associated with G2 cell cycle arrest, impaired cytokinesis and finally apoptosis (Zhong et al, 2005;Rosenstiel et al, 2008;2009b;Snyder et al, 2010;Vashistha et al, 2008). A synergistic effect of nef and vpr was observed in a study which showed that mice with both nef and vpr expression developed more severe nephropathy (Zuo et al, 2006).…”
Section: Amjmentioning
confidence: 99%